Academically gifted African American male college students - Bonner, Fred A. (Praeger/ABC-CLIO, 2010)
At a time when so many studies of African American students focus on the factors of failure, Academically Gifted African American Male College Students fills a conspicuous void in the research literature on post-secondary education by focusing on success. Like no other work before it, this remarkable study goes deep inside the experiences of academically gifted African American men who successfully navigate their way through rigorous college-level programs.